2015
DOI: 10.4172/2376-0281.1000145
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Versus Unilateral Upper Extremity Training on Upper Limb Motor Activity in Hemiplegia

Abstract: Background: Upper extremity paresis post stroke is an important contributor to disability and task oriented rehabilitation aims at compensating loss of function in the affected upper extremity. Bilateral arm training focuses on coupling both the extremities during treatment to gain symmetrical and synchronous movement in both the limbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…After ischemic coronary heart disease, stroke is the most typical purpose of mortality global, having brought on round 5.7 million deaths in, of which greater than 80% took place in low and middle earnings countries (LMIC). In addition, estimates showed that there may be 62 million survivors of stroke global, many of whom are likely to be disabled, with up to a third living with severe disability (12).…”
Section: Introductionmentioning
confidence: 99%
“…After ischemic coronary heart disease, stroke is the most typical purpose of mortality global, having brought on round 5.7 million deaths in, of which greater than 80% took place in low and middle earnings countries (LMIC). In addition, estimates showed that there may be 62 million survivors of stroke global, many of whom are likely to be disabled, with up to a third living with severe disability (12).…”
Section: Introductionmentioning
confidence: 99%
“…Both bilateral and unilateral functioning should be measured for patients with stroke because movement pattern and neurological improvement vary based on stroke type. For instance, unilateral upper extremity function emphasizes using the nonparetic or paretic limb, thereby emphasizing neural effects of the ipsilateral or contralateral hemisphere, specifically (Syed et al, 2015). In contrast, bilateral upper extremity function encourages the simultaneous use of the limbs on both the affected and nonaffected sides, which requires enhanced interhemispheric coupling and neural cross-talk (Syed et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, unilateral upper extremity function emphasizes using the nonparetic or paretic limb, thereby emphasizing neural effects of the ipsilateral or contralateral hemisphere, specifically (Syed et al, 2015). In contrast, bilateral upper extremity function encourages the simultaneous use of the limbs on both the affected and nonaffected sides, which requires enhanced interhemispheric coupling and neural cross-talk (Syed et al, 2015). Thus, it is important to precisely measure residual bilateral upper extremity functions to establish tailored treatment plans for patients with stroke.…”
Section: Introductionmentioning
confidence: 99%